Avaliação ecotoxicológica de nanopartículas de prata biogênica e sintética e de sal de prata sobre estágios embrionários de ouriço do mar Echinometra lucunter - Silva, Mariana Bruni Marques do Prado e [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Nanotechnology has allowed the development of nanoscale materials, as well as studies on their properties and production. The silver nanoparticle (AgNP) has antibacterial properties and has been widely produced and incorporated in many materials. AgNP can be synthetized biogenically and/or synthetically, generating products with different physico-chemical properties. AgNPs can reach the environment in different ways, as a result of human activity, where they can harm non-target organisms. However, the ecotoxicological effects of AgNPs on aquatic environments are not studied. This study aimed to evaluate and compare the ecotoxicological effects of synthetic and biogenic AgNP and the Ag in the form of salt on the embryos of the sea urchin Echinometra lucunter. Adult individuals of E. lucunter were collected and acclimated in laboratory; then their spawning was induced, and the eggs were fertilized in vitro. The eggs were exposed to different AgNP, AgNO3, SiNC and SiNC-Ag concentrations for 48h, under physical-chemical controlled conditions. Next, the content of each replicate was fixed and the embryolarval development was analyzed. The data were analyzed by analysis of variance followed by Dunnet’s t-test, and the inhibition concentration to 50% of embryos (IC50) was calculated by linear interpolation. The obtained IC50 values were 0.0083 μg/L to synthetic AgNP, 0.205 μg/L to biogenic AgNP, 0.062 μg/L to AgNO3, 0.0076 μg/L to SiNC, and 0.0068 to SiNC-Ag. All the compounds tested were toxic to E. lucunter embryos, even in low concentrations (since <0.01 μg/L of synthetic AgNP, SiNC and SiNC-Ag, and 0.1 μg/L of biogenic AgNP and AgNO3). It is necessary to determine the limit concentration that cannot harm marine animals, considering that at 1 μg/L there was a lack of embryonic development in every compound tested.

A nanotecnologia tem permitido que materiais em nano escala sejam estudados, desenvolvidos e produzidos. A nanopartícula de prata (AgNP) possui propriedades antibacterianas e tem sido amplamente produzida e incorporada em muitos materiais. É possível sintetizar a AgNP biogenicamente e sinteticamente, gerando produtos com propriedades físico-químicas diferentes. As AgNP podem chegar ao ambiente, podendo atingir e prejudicar organismos não-alvos, porém seus efeitos ecotoxicológicos e consequências em ambientes aquáticos são pouco estudados. Este estudo visou avaliar e comparar os efeitos ecotoxicológicos das AgNP sintéticas e biogênicas e da prata em forma de sal, nanocápsulas mesoporosas de sílica (SiNC) e SiNC incrustradas com prata sobre embriões de ouriço do mar Echinometra lucunter. Para tal, indivíduos de E. lucunter foram coletados e aclimatados em laboratório, onde foi feita a indução da desova e a fecundação in vitro. Os ovos recém-fecundados foram expostos, sob condições físico-químicas controladas, a diferentes concentrações de AgNP, AgNO3, SiNC e SiNC-Ag, durante o período de 48 horas. Em seguida o conteúdo de cada réplica foi fixado e observado o sucesso do desenvolvimento embriolarval dos organismos. Os dados foram analisados por análise de variância seguida de teste de Dunnett, e foram calculadas as concentrações de inibição a 50% dos embriões (CI50) por interpolação linear. Foram obtidas CI50 de 0,0083 μg/L para AgNP sintéticas 0,205 μg/L para AgNP biogênica, 0,062 μg/L para AgNO3, 0,0076 μg/L para SiNC e 0,0068 μg/L para SiNC-Ag. Os resultados obtidos mostram que todos os compostos são tóxicos aos embriões de E. lucunter em concentrações baixas (a partir de < 0,01 μg/L para AgNP sintéticas, SiNC e SiNC-Ag e 0,1 μg/L para AgNP biogênicas e AgNO3). Há necessidade de determinação da concentração limite para que não haja prejuízo à fauna marinha, já que a partir da concentração 1 μg/L não é observado desenvolvimento de nenhum embrião para nenhum dos compostos testados.
Ecotoxicological evaluation of biogenic and synthetic silver nanoparticles and silver salt over sea urchin Echinometra lucunter embryo stages
Keywords: Silver nanoparticle; Toxicity; Contamination; Antimicrobial effect; Nanopartícula de prata; Toxicidade; Echinometra lucunter; Contaminação; Efeito antimicrobiano